Changing the culture is a marathon not a sprint - Jenna Dixon; Susan J. Elliott (Allergy, Asthma & Clinical Immunology, 2019)
Abstract Integrated knowledge translation (IKT) is built upon the premise that involving knowledge users as partners in the research process will result in science that is more relevant to the public and therefore will have greater impact. Drawing on our experiences with a large and multifaceted IKT food allergy research program we highlight the disjuncture between the goals of IKT and the nature of basic science research, most notably the long timelines before research is ready for translation. Our partner consultations concluded that IKT success should be measured in a different way. That is, it should not be about informing an immediate gap in the translation of food allergy findings but about building relationships between our partners, greater awareness, understanding and knowledge about the nature of science and IKT, and ultimately helping to create better policy and science down the road. It is the recognition that it behooves us as scientists to be able to answer those “why” questions. We call for other researchers to consider the success of IKT beyond the short term timelines of any one research project but instead as an avenue to build partnerships, innovate thinking about research questions and to maximize choice and minimize risk for individuals in Canada and beyond affected by food allergy.